Factor of intention to use Pustaka Negeri Sarawak E-Services amongst State Civil Servant in Wisma Bapa Malaysia, Kuching Sarawak / Muhamad Daneal Jamali - Jamali, Muhamad Daneal (2017)
Malaysia government has been investing huge funding initiatives in building e-services for its national, state and municipal libraries. This initiative is in support of the national aspiration for creating knowledge-based society. From the perspective ofthe libraries, an online presence is pivotal in support to the increased rate of Internet usage among their stakeholders, academics and student alike, therefore the result of adopting electronic services has changed both the means of communicating with the users and nature ofthe service itself. The purpose ofthis research was to identify the factors of Intention to Use libraries’ e-services specifically Pustaka Negeri Sarawak E-services by selected group of users; the State Civil Servant in Wisma Bapa Malaysia, Kuching Sarawak. To answer this question, a survey was designed and conducted amongst State Civil Servant in Wisma Bapa Malaysia, Kuching Sarawak (n=151). This research allows drawing the findings of three emerging factors of Intention to Use which are Interface Effectiveness (IU), Confidence in System (CS) and Effectiveness of Use (EU). The most significant factors towards Intention to Use Pustaka Negeri Sarawak E Services amongst State Civil Servant in Wisma Bapa Malaysia, Kuching Sarawak are Effectiveness of Use and Interface Effectiveness. From the perspective of the user-centric approach, we identified the function of State Civil Servant in Wisma Bapa Malaysia Kuching Sarawak at increasing the Intention to Use Pustaka Negeri Sarawak E-Services by involving users’ in the designing phases of the libraries’ e-services.